POTENTIAL BIOMONITORS FOR ATMOSPHERIC POLLUTION - Daud, M.; Waheed, S.; Siddique, N.; Ahmad, S.; Samad, N. S. (The Nucleus, 2020)
Undesirable influence of air pollution on the human health and the ecosystem has led to an increased interest in toxic emissions monitoring programs. To fingerprint the countrywide and regional transboundary pollution profiles, extensive direct monitoring network is needed, which is very expensive and laborious. Plant leaves, mosses and epiphytic lichens are regarded as potential alternate tools for monitoring levels of atmospheric pollution. Mosses and epiphytic lichens, unlike higher plants have no roots and waxy cuticle nor stomata; hence for mineral nutrition they are largely dependent on wet or dry deposition from the atmosphere. This unique feature has been exploited to predict the pollution levels of the areas in which they are grown by analyzing the embodied toxic elements. Sampling of such naturally growing bioindicators is relatively easier and no sophisticated equipment are needed. The aim of this study was to obtain insight into the response of such plants, when exposed in the vicinity of highly polluted areas and subsequently to confirm the agreement between elemental levels in bioindicators and those measured in atmospheric deposition collected directly with air samplers. INAA and AAS techniques were employed for multielement analysis of exposed samples. Definite influence of pollution on the studied bioindicators was observed for some of the heavy metals like Cd, Cu, Pb and Zn. Results obtained in this work indicate the feasibility of using Broussonetia Papyrifera leaves and moss as bioindicators for environmental pollution monitoring. This pattern was also confirmed by analyzing the air particulate matters (APM) collected on filters using Gent air sampler.